Role of soluble urokinase plasminogen activator receptor in critically ill children with hospital-acquired pneumonia: an observational study in hospital with controls - Nagwan Yossery Saleh; Shimaa Elshafy Soliman; Mohammed Adel Aboukoura; Mohamed Ibrahim Garib (BMJ Publishing Group, 2024)
Background Diagnosing hospital-acquired pneumonia (HAP) (ventilator-associated pneumonia (VAP) and non-ventilator associated pneumonia (Non-VAP)) is still a hot issue. Soluble urokinase plasminogen activator receptor (suPAR) is prognostic in critically ill children with sepsis regarding mortality prediction. Our aim was to evaluate suPAR levels in children with HAP.Methods An observational, prospective study was conducted on 45 children diagnosed HAP (VAP and Non-VAP) and 40 healthy controls. Paediatric Sequential Organ Failure assessment Score (pSOFA) was assessed for each patient. Plasma suPAR levels were measured with ELISA on the day of diagnosis.Results On comparison levels of plasma suPAR for the children with HAP with the healthy control group, no statistically significant difference was observed (148 pg/mL (22.4-1939.7) and 184.4 pg/mL (31.6-1311.7), respectively, (p=0.32). suPAR was significantly increased in children with elevated pSOFA score on the day of diagnosis of pneumonia (p=0.034). suPAR was significantly increased in children with shock (p=0.005). suPAR levels was negatively correlated with oxygen saturation (rs=0.31,p=0.048). suPAR was not significantly correlated with C reactive protein.Conclusions suPAR can be used as a predictor for severity of illness in children with HAP. We firmly know that plasma suPAR, a novel marker, could indicate the disease if carried out on larger patient groups.